Maqāṣid al-Sharīʿah Compliance in Indonesian Islamic Banks: Accounting Evaluation of the Vision and Mission - Rifqiawan, Raden Arfan (Ekonomi Syariah IAIN Kudus, 2025)
The purpose of this study is to assess the extent of alignment between the vision and mission of Indonesian Islamic banks and the maqāṣid al-sharīʿah, with a focus on welfare, justice, and compliance in Islamic finance. This research would provide essential information to verify whether Islamic banks’ strategic plans benefit them more in achieving profit, while neglecting the core values of sharia principles. The study design is a descriptive qualitative study with a document analysis approach. The data was elicited from the official vision and mission documents of the selected major Islamic banks in Indonesia. Through document triangulation, the analysis verifies conformity with the five principles of maqāṣid al-sharīʿah: the protection of religion (al-dīn), life (al-nafs), intellect (al-‘aql), lineage (al-nasl), and property (al-māl), assissting to identify areas that are sufficiently operational and those that require further confirmation. Based on the study, most Islamic banks have sufficiently aligned with the following code of principles, where the religious aspect is reflected in various sharia-compliant products, supervised by Sharia Supervisory Boards, and communicated to customers. The property side has been reflected in transparent risk management and well-defined contracts. However, the bank's strategy remains profit-oriented rather than community-centered, lacks prominent communication with customers through monitoring, and is still not process-driven.